A Surface Reconstruction Route to High Productivity and Selectivity in CO2 Electroreduction toward C2+ Hydrocarbons. Issue 49 (9th October 2018) - Kibria, Md Golam; Dinh, Cao‐Thang; Seifitokaldani, Ali; De Luna, Phil; Burdyny, Thomas; Quintero‐Bermudez, Rafael; Ross, Michael B.; Bushuyev, Oleksandr S.; García de Arquer, F. Pelayo; Yang, Peidong; Sinton, David; Sargent, Edward H.
Abstract: Electrochemical carbon dioxide reduction (CO2 ) is a promising technology to use renewable electricity to convert CO2 into valuable carbon‐based products. For commercial‐scale applications, however, the productivity and selectivity toward multi‐carbon products must be enhanced. A facile surface reconstruction approach that enables tuning of CO2 ‐reduction selectivity toward C2+ products on a copper‐chloride (CuCl)‐derived catalyst is reported here. Using a novel wet‐oxidation process, both the oxidation state and morphology of Cu surface are controlled, providing uniformity of the electrode morphology and abundant surface active sites. The Cu surface is partially oxidized to form an initial Cu (I) chloride layer which is subsequently converted to a Cu (I) oxide surface. High C2+ selectivity on these catalysts are demonstrated in an H‐cell configuration, in which 73% Faradaic efficiency (FE) for C2+ products is reached with 56% FE for ethylene (C2 H4 ) and overall current density of 17 mA cm ‐2 . Thereafter, the method into a flow‐cell configuration is translated, which allows operation in a highly alkaline medium for complete suppression of CH4 production. A record C2+ FE of ≈84% and a half‐cell power conversion efficiency of 50% at a partial current density of 336 mA cm ‐2 using the reconstructed Cu catalyst are reported. Abstract : Electrochemical CO2 reduction is a promising route to facilitate large‐scale storage of intermittent renewable electrons in the form of chemical bonds. A facile wet‐oxidation approach to enhance the CO2 ‐reduction selectivity toward C2+ products on a copper‐chloride‐derived catalyst is reported. The C2+ Faradaic efficiency of ≈84% at a partial current density of 336 mA cm −2 is demonstrated.